2021
DOI: 10.1371/journal.pone.0253933
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sex on use of low tidal volume ventilation in invasively ventilated ICU patients—A mediation analysis using two observational cohorts

Abstract: Background Studies in patients receiving invasive ventilation show important differences in use of low tidal volume (VT) ventilation (LTVV) between females and males. The aims of this study were to describe temporal changes in VT and to determine what factors drive the sex difference in use of LTVV. Methods and findings This is a posthoc analysis of 2 large longitudinal projects in 59 ICUs in the United States, the ‘Medical information Mart for Intensive Care III’ (MIMIC III) and the ‘eICU Collaborative Rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
5
11
0
Order By: Relevance
“…An earlier analysis showed that a one SD increases in V T , PBW meant an increase of 28% in 28-day mortality ( 5 ). The finding that females received ventilation with a higher median V T than males in this cohort is in line with results from several investigations originating from before the COVID-19 pandemic ( 13 16 , 44 ). It interesting to note that V T , in both females and males, was lower than in those previous cohorts, suggesting a temporal trend toward the use of lower V T in critically ill patients ( 16 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…An earlier analysis showed that a one SD increases in V T , PBW meant an increase of 28% in 28-day mortality ( 5 ). The finding that females received ventilation with a higher median V T than males in this cohort is in line with results from several investigations originating from before the COVID-19 pandemic ( 13 16 , 44 ). It interesting to note that V T , in both females and males, was lower than in those previous cohorts, suggesting a temporal trend toward the use of lower V T in critically ill patients ( 16 ).…”
Section: Discussionsupporting
confidence: 91%
“…The finding that females received ventilation with a higher median V T than males in this cohort is in line with results from several investigations originating from before the COVID-19 pandemic ( 13 16 , 44 ). It interesting to note that V T , in both females and males, was lower than in those previous cohorts, suggesting a temporal trend toward the use of lower V T in critically ill patients ( 16 ). Despite the improved use of LTVV, however, differences between females and males persist.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations